Evaluation of some cardiac markers in relation to COVID-19 mRNA vaccine - AL-Eqabi, Ahmed; Al-Azzawi, Buthainah (Journal of Biomedicine and Biochemistry, 2022)
Background: Acute myocardial infarction (AMI) is a dangerous cardiovascular illness that has a significant impact on people's health. Several biomarkers, including Myoglobin and troponin I (cTnI) were utilized to diagnose AMI in recent decades. The Troponin I (cTnI) was designated as the "gold standard" cardiac biomarker for the prediction of cardiomyopathy. It's a heart muscle regulating protein found on normal myocyte actin filaments. When cardiac muscles are injured, cTnI, one of the main subunits of the cardiac troponin complex, is released into the circulation (e.g., myocardial infarction). Myoglobin denoted by (symbols Mb and MB) seems to be an iron- and o2-binding protein present in the vertebrate heart and skeletal muscle tissues and, more specifically, nearly all mammals. In humans, MB is only present in the bloodstream following muscle damage. Its primary function is to supply myocytes with oxygen. Also essential to nitric oxide hemostasis was myoglobin. Additionally, it facilitates the detoxification of response oxygen molecules from the body. MB is accountable for most vertebrate muscles' red hue.The aim: To assess the difference in the level of (MYOGLOBIN and TROPONIN_I) between patients with and without mRNA Vaccination.Methods: This study included 125 patients (65 male and 60 female) with vaccinated and non-vaccinated covid-19 with an age range of 20–69 years. These patients are divided into two main groups: 1. vaccinated (vaccinated with COVID-19 infection, vaccinated without COVID-19 disease, vaccinated recovered from the CoV-19 virus),2. unvaccinated (infected with the CoV-19 virus and non-vaccinated, recovered from covid-19 and unvaccinated). The outcome is measured using the Enzyme-linked immunosorbent assay (ELISA) technique. This study was conducted during the period from November 2021 to May 2022 at the Martyr Dr. Fairouz General Hospital, Wasit governorate, Iraq.Results: Estimation of serum Troponin I and Myoglobin concentration showed that concentrations of Troponin I and Myoglobin were significantly higher (P